Adipocyte death defines macrophage localization and function in adipose tissue of obese mice and humans - Saverio Cinti; Grant A. Mitchell; Giorgio Barbatelli; Incoronata Murano; E Ceresi; Emanuela Faloia; Shupei Wang; Mélanie Fortier; Andrew S. Greenberg; Martin S. Obin (2005)
Macrophage infiltration of white adipose tissue (WAT) is implicated in the metabolic complications of obesity. The precipitating event(s) and function(s) of macrophage infiltration into WAT are unknown. We demonstrate that >90% of all macrophages in WAT of obese mice and humans are localized to dead adipocytes, where they fuse to form syncytia that sequester and scavenge the residual "free" adipocyte lipid droplet and ultimately form multinucleate giant cells, a hallmark of chronic inflammation. Adipocyte death increases in obese (db/db) mice (30-fold) and humans and exhibits ultrastructural features of necrosis (but not apoptosis). These observations identify necrotic-like adipocyte death as a pathologic hallmark of obesity and suggest that scavenging of adipocyte debris is an important function of WAT macrophages in obese individuals. The frequency of adipocyte death is positively correlated with increased adipocyte size in obese mice and humans and in hormone-sensitive lipase-deficient (HSL-/-) mice, a model of adipocyte hypertrophy without increased adipose mass. WAT of HSL-/- mice exhibited a 15-fold increase in necrotic-like adipocyte death and formation of macrophage syncytia, coincident with increased tumor necrosis factor-alpha gene expression. These results provide a novel framework for understanding macrophage recruitment, function, and persistence in WAT of obese individuals.